Pengaruh Budaya Organisasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan Dengan Motivasi Sebagai Variabel Moderating Pada Toko Taqwa Mulia Batanghari - Suryadi; Slamet Tedy Siswoyo; Nila Tri Lestari (Jurnal Manajemen DIVERSIFIKASI, 2024)
The purpose of this research was to find out whether there was an influence of organizational culture and working environment towards the employee performance with motivation as a moderating variable at the taqwa mulia store at Batanghari sub-district. The research Methods applied Descriptive and quantitative approaches. The population and sample were the employees of taqwa mulia shop at Batanghari sub-district, with a total of 38 employees. The data collection technique used a questionnaire. The research data were analyzed by testing the prerequisites instrument, namely the Pearson product moment validity test. Furthermore, the reliability test used the Cronbach alpha test. Furthermore, to test the research hypothesis, the researcher utilized normality test, linearity test and homogeneity test. Next, a multiple linear regression test, T test, F test were performed and tested with the moderating variable in order to analyze the data of this study. Furthermore, data analysis were undertaken through moderated regression analysis (MRA) with the SPSS program. Based on the results of this study, it showed that: 1) organizational culture influenced the employee performance. 2) the working environment had a positive effect on the employee performance, 3) the organizational culture which was moderated by motivational variables had an acceptable value, so it can be concluded that motivational variables are able to moderate organizational culture on the employee performance. 4) the working environment is moderated by the variable motivation which has an acceptable value. Based on these results it can be concluded that the motivational variable is able to moderate organizational culture on employee performance. Keywords ; Organizational Culture, Work Environment, Employee Performance, Motivation